Market Access for Developing Country Exports : Selected Issues. (Policy Papers; Policy Paper ;, 2002)
In this paper, the World Bank and the International Monetary Fund have drawn together available research findings on the benefits of trade liberalization as well as on the obstacles to trade-oriented development.